Factors relating to the development of respiratory symptoms in coffee process workers. Issue 5 (May 1991) - Thomas, K E; Trigg, C J; Baxter, P J; Topping, M; Lacey, J; Crook, B; Whitehead, P; Bennett, J B; Davies, R J
Abstract : After several cases of occupational asthma had been reported in a coffee processing factory in England, 197 coffee workers representing 80% of the production workforce were studied to determine the factors affecting the development of work related respiratory symptoms of wheeze, cough, and dyspnoea. Two computer administered questionnaires concerning the presence of respiratory symptoms and the occurrence of work related respiratory symptoms were used. Workers underwent skin prick testing to green coffee bean extract (GCB) and 11 common inhalant allergen extracts and bronchial provocation testing with methacholine. The presence of specific immunoglobulin E (IgE) antibodies to GCB and castor bean extract (CAB) were determined by a radioallergosorbent test (RAST). The prevalence of work related respiratory symptoms was 12.7%, bronchial hyperresponsiveness 30%, atopy 54%, positive GCB skin prick test 14.7%, positive GCB RAST 14%, and positive CAB RAST 14.7%. None of the workers was sensitised to fungi present in the factory and the numbers of certain species of fungi, despite being greater than may be found out of doors or in an uncontaminated indoor environment, were fewer than are generally associated with the presence of work related respiratory symptoms among agricultural workers. Storage mites were not isolated. Green coffee bean extract and CAB RAST were significantly correlated using the McNemar test but there was limited allergenic cross reactivity in RAST inhibition studies of the two extracts. The only factors that were significantly and independently associated with work related symptoms were CAB RAST and duration of employment. Bronchial hyperresponsiveness was not independently associated with work related respiratory symptoms. The significant independent associations of bronchial hyperresponsiveness included GCB RAST, duration of employment, and resting forced expiratory volume in one second. Exposure to CAB, a highly potent antigen, may be overriding the effects of other factors such a GCB, atopy, bronchial hyperresponsiveness, and smoking. This study suggests that CAB contamination remains a potential problem in the coffee processing industry and all efforts to eliminate it from the working environment should continue.